Depresi dan kualitas hidup pasien diabetes mellitus tipe 2 - Elina Chrisniati; Carla Raymondalexas Marchira; Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Depression and the quality of life among patients with type 2 diabetes mellitus in Sardjito hospitalPurposeThe purpose of this study was to assess the association between depression and quality of life among patients with type 2 diabetes mellitus in Dr. Sardjito Hospital.MethodsTwo questionnaires were distributed among 152 patients between May and June 2016 using the Beck depression inventory and diabetes quality of life clinical trial. Univariable, bivariable, and multivariable linear regression analyses were used to explore associations.ResultsThis study found quality of life was 67.37. There was association between depression and quality of life, while sex, complications, age and education level were not significantly correlated. The simultaneous influence of the variable of depression, work and duration of illness to mean of quality of life equaled to 28%.ConclusionComprehensive services are needed to reduce depression and improve the quality of life among patients with type 2 diabetes mellitus. People suffering from type 2 diabetes who do not experience depression have a better quality of life than people with type 2 diabetes who experience stress.